Multimorbidity: the case for prevention. Issue 3 (5th October 2020) - Head, Anna; Fleming, Kate; Kypridemos, Chris; Pearson-Stuttard, Jonathan; O'Flaherty, Martin
Abstract : Multimorbidity is of increasing concern for healthcare systems globally, particularly in the context of ageing population structures, such as in the European Union and the UK. Although there is growing attention on developing strategies to manage the health and healthcare burden of older patients with multimorbidity, little research or policy focus has been placed on how to best prevent the development of multimorbidity in future generations. In this research agenda piece, we argue for a shift from a sole focus on the management of multimorbidity in old age to a multimorbidity agenda that considers prevention and management throughout the life-course.